The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1143/jpsj.78.084709
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study on the Magnetic Anisotropy in Multiferroic PbVO3 and BiCoO3

Abstract: Magnetic anisotropy energies (MAE) of multiferroic PbVO 3 and BiCoO 3 are evaluated from firstprinciples density functional calculations. Even though both oxides have similar crystal and electronic structures, calculated easy axes of spin are different: [110] in PbVO 3 and [001] in BiCoO 3 . To explain the difference, the origin of MAE is discussed with a perturbation theory by taking into account of the electronic structure obtained by the first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The present observation of C-AF state as a magnetic ground state for PVO is consistent with experimental observation of a two-dimensional C-AF phase and also with other theoretical studies. 14,17 To identify the exact composition where the nonmagnetic-to-magnetic transition occurs, we have plotted Δ E versus x (where Δ E = E C-AF – E NM ) for the ferroelectric phase, as shown in Figure S7 in the Supporting Information. The energy difference increases linearly as the concentration of V increases due to the increase in localized d electrons density per cell making the antiferromagnetic state more stable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present observation of C-AF state as a magnetic ground state for PVO is consistent with experimental observation of a two-dimensional C-AF phase and also with other theoretical studies. 14,17 To identify the exact composition where the nonmagnetic-to-magnetic transition occurs, we have plotted Δ E versus x (where Δ E = E C-AF – E NM ) for the ferroelectric phase, as shown in Figure S7 in the Supporting Information. The energy difference increases linearly as the concentration of V increases due to the increase in localized d electrons density per cell making the antiferromagnetic state more stable.…”
Section: Resultsmentioning
confidence: 99%
“…The present observation of C−AF state as a magnetic ground state for PVO is in consistent with experimental observation of a two−dimensional C−AF phase and also with other theoretical studies. 14,17 To identify the exact composition where the non−magnetic to magnetic transition happens, we have plotted ∆E vs x (where ∆E = E C−AF − E N M ) for the ferroelectric phase and given in the supporting information Fig. S7.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…The PbVO 3 tetragonal perovskite (P4mm) (T-phase) was synthesized recently at high pressures and suggested to be a candidate multiferroic with a two-dimensional C-type antiferromagnetism (C-AFM) ordering and a large ferroelectric polarization [6][7][8]. The PbVO 3 T-phase is isostructural with PbTiO 3 , but exhibits a more pronounced structural distortion and a much larger unit cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…From the X-ray structural analyses and X-ray emission spectroscopy, it is suggested that the spin-state change from LS to HS occurs due to this large structural change. Thus, this material is expected to be a novel class of ME materials, [36][37][38][39][40][41] in which the electric polarization couples with the spin-state degree of freedom, and is expected to open a new route to the multiferroics near the boundary between the band and Mott insulators.In this Letter, motivated by the experiments in BiCoO 3 , we examine the magnetic and dielectric properties in the spinstate transition system. We introduce a strong coupling model, derived from the two-orbital Hubbard model, interacting with the FE-type lattice distortion, and investigate the ground-state and finite-T properties using the mean-field approximation.…”
mentioning
confidence: 99%
“…From the X-ray structural analyses and X-ray emission spectroscopy, it is suggested that the spin-state change from LS to HS occurs due to this large structural change. Thus, this material is expected to be a novel class of ME materials, [36][37][38][39][40][41] in which the electric polarization couples with the spin-state degree of freedom, and is expected to open a new route to the multiferroics near the boundary between the band and Mott insulators.…”
mentioning
confidence: 99%